Systematic chemical functionalization of hybrid molecule–surface interfaces. Issue 11 (1st October 2013) - Caciuc, V.; Lennartz, M. C.; Atodiresei, N.; Tsukamoto, S.; Karthäuser, S.; Blügel, S.; Frauenheim, Thomas; Niehaus, Thomas; Repp, Jascha; Richter, Klaus; Weber, Heiko
<x xml:space="preserve">Abstract</x> In this article, we briefly overview our experimental and theoretical studies aimed to investigate the electronic structure and the transport properties of several carboxylates chemisorbed on the Cu(110) surface. In particular, we have theoretically explored the possibility to chemically functionalize a carboxylate–Cu(110) system to specifically tune its electronic structure. Experimentally, it could be proven that the transport properties of the carboxylate–Cu(110) interface indeed revealed specific features in the d<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3v1brn2z" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />I/dV</alternatives> spectra corresponding to the used functionalization process. Moreover, the d<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3v1brn0v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />I/dV</alternatives> spectra can be used to identify specific adsorption geometries or conformations of carboxylates on Cu(110). Furthermore, transport calculations for molecules with different anchoring groups between two Cu(110) electrodes are also discussed. <inline-graphic xlink:href="ark:/27927/pgg3v1bmqh7" content-type="pssb201349076-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Schematic view of a STM tip probing a carboxylate molecule chemisorbed on the Cu(110) surface with the corresponding energy level alignment in the case of a zero bias voltage.